Proposta de implantação da escala de alerta precoce modificado (MEWS) em unidades de internação hospitalar - Sehnem, Gabriela Corrêa (Universidade do Vale do Rio dos Sinos, 2016)
INTRODUCTION: Patients hospitalized in hospitalization units are susceptible to worsening of their clinical condition. The identification of these warning signs is usually done by the nurse and can be performed by the modified Early Warning Score (MEWS) tool. OBJECTIVE: To elaborate a proposal to implement the MEWS scale for the activation of the rapid response team (TRR) in clinical and surgical hospital admission unit of a private hospital in Porto Alegre/RS. METHOD: Retrospective cohort study from January to August 2015, conducted in 115 TRR service records. The vital signs were evaluated at the time of the call, in addition to 24 and 48h before the activation to determine the MEWS value, as recommended. Data as the reason for the call, outcomes, sex and age were collected to present the appropriate associations. ETHICAL ASPECTS: The project was approved by the Ethics and Research Committee of UNISINOS and HED with opinion № 1,507,674. RESULTS: 39% of the patients (of the 115 analyzed sheets) ) Were transferred to the Intensive Care Unit. A MEWS value of four presents a relative risk for this outcome of 1.38 (95% CI 1.04 to 1.84). From this data the MEWS was inserted in the TRR protocol and a call flow chart was proposed using the scale. CONCLUSION: The use of MEWS in hospitalization units as an inpatient evaluation tool implies the detection of warning signs and predicts Severity of the case and, consequently, is related to a better clinical outcome. In addition, the scale assists in the organization of the nursing work process and facilitates the care provided to the patient by the nurse.
Keywords: MEWS - Modified Early Warning Score; Times de resposta rápida; Unidades de terapia Intensiva; Avaliação em enfermagem; Emergency response teams; Intesive care unit; Nursing evaluation; ACCNPQ::Ciências da Saúde::Enfermagem